The perception towards the uniqueness of Kelantan's traditional desserts / Nurfarahin Aloha - Aloha, Nurfarahin (2014)
Traditional food has long been an identity to all races because of uniqueness and specialty. Starts from dishes, appetizers until the desserts, it was across cultures and races in this country. There are many types of traditional food in Malaysia such as dishes and desserts. Malaysian traditional desserts originated from two distinct places, West Malaysia and East Malaysia. They are many varieties of desserts which can be found in all states in Malaysia. One of the famous Malaysian traditional desserts comes from Kelantan. Kelantan is not only known for its variety of cultures but also famous for its unique food. For centuries, the originality of the taste made by the Kelantan's people is not changed. Kelantan has a diversity of course famous traditional cuisine that is certainly alluring with its own flavor and taste. The purpose of my research is to find out the public perception around Malacca City towards Kelantan's traditional desserts. There are many types of perceptions that may be concluded from public towards Kelantan's traditional desserts. Examples of perceptions is public's not familiar with the desserts and public think that packaging of the desserts not attractive and convincing. The research method consists of primary and secondary data such as distribute questionnaires among public around Malacca City, ,observation and document review from online or offline sources. The information gathered is important to bring some ideas to conduct the research. The result and finding will be discussed for achieving goals of the research. The research also will briefly explain on the recommendation for further research.